PENGARUH KESADARAN, PENGETAHUAN DAN PEMAHAMAN PERPAJAKAN, KUALITAS PELAYANAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK - Putri, Kadek Juniati; Setiawan, Putu Ery (E-Jurnal Akuntansi, 2017)
This research aimed to determine the effect of taxpayer awareness, knowledge and understanding of regulations, taxation, quality of service and tax penalties on tax compliance on the Tax Office (KPP) Pratama East Denpasar. The theory used in this study are attribution theory (atribution theory), contingency theory and the theory of perceived behavior (TPB). The population in this study include individual taxpayers registered at the Tax Office Pratama East Denpasar number 100.703 taxpayers. The samples used in this study were 100 respondents with incidental sampling technique sampling method. The data collection was conducted by questionnaire. Data analysis technique used is multiple linear regression. The results showed that the taxpayer awareness, knowledge and understanding of regulations, taxation, quality of service and tax penalties positive effect on tax compliance.
Keywords: taxpayer awareness; knowledge and understanding of regulations taxation; quality of service; tax penalties; tax compliance